2022
DOI: 10.1111/phn.13098
|View full text |Cite
|
Sign up to set email alerts
|

“It's not right”: Nurse perspectives on rural hospital closures: A qualitative study

Abstract: Objective(s) Despite providing lifesaving care, 106 rural hospitals have closed in the United States since 2010. Although the role of rural hospital nursing is central, limited information is available about closures from a nursing lens. The purpose was to describe rural hospital closure contributors, processes, and outcomes from the perspective of licensed rural nurses in a hospital during its closure. Design This cross‐sectional study used a retrospective, qualitative design grounded in subjective epistemolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…30 In addition to quantitative evidence in the availability of providers, qualitative assessments of nurses have described their perceptions on rural hospital closure. 31 Nurses have highlighted personal job loss, loss of well-being, and loss of ability to apply their expertise as key issues related to rural hospital closure. In addition to nursing insight on the impact of closures on their workforce, the same study identified their perception of rural hospital closure's impact on the local community.…”
Section: Workforce and Community Impactmentioning
confidence: 99%
See 3 more Smart Citations
“…30 In addition to quantitative evidence in the availability of providers, qualitative assessments of nurses have described their perceptions on rural hospital closure. 31 Nurses have highlighted personal job loss, loss of well-being, and loss of ability to apply their expertise as key issues related to rural hospital closure. In addition to nursing insight on the impact of closures on their workforce, the same study identified their perception of rural hospital closure's impact on the local community.…”
Section: Workforce and Community Impactmentioning
confidence: 99%
“…services, overall inaccessibility of services, and concerns around adverse impacts on quality of care. 31 Another focus group study of community members in a small community that experienced hospital closure found that among the 37 people interviewed, sentiments centered around fear and anger-with feelings of abandonment by the health system, fear regarding new travel distance for care, and confusion regarding where to obtain care going forward. 32…”
Section: Workforce and Community Impactmentioning
confidence: 99%
See 2 more Smart Citations